2019
DOI: 10.1038/s41598-019-42862-y
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal characterization of the Non-Cystic Fibrosis Bronchiectasis airway microbiome

Abstract: A diverse microbiota exists within the airways of individuals with non-cystic fibrosis bronchiectasis (nCFB). How the lung microbiome evolves over time, and whether changes within the microbiome correlate with future disease progression is not yet known. We assessed the microbial community structure of 133 serial sputa and subsequent disease course of 29 nCFB patients collected over a span of 4–16 years using 16S rRNA paired-end sequencing. Interestingly, no significant shifts in the microbial community of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 45 publications
4
42
1
Order By: Relevance
“…complex, contains multiple bacterial genera and is highly individual [46,47]. A recent longitudinal study by WOO et al [48] followed 29 bronchiectasis patients for up to 16 years and demonstrated remarkable stability of the microbiome over many years of follow-up. The microbiomes of Pseudomonas-and Haemophilus-dominated patients were widely divergent and patients maintained similar profiles over time despite antibiotic treatments [48].…”
Section: Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…complex, contains multiple bacterial genera and is highly individual [46,47]. A recent longitudinal study by WOO et al [48] followed 29 bronchiectasis patients for up to 16 years and demonstrated remarkable stability of the microbiome over many years of follow-up. The microbiomes of Pseudomonas-and Haemophilus-dominated patients were widely divergent and patients maintained similar profiles over time despite antibiotic treatments [48].…”
Section: Microbiotamentioning
confidence: 99%
“…A recent longitudinal study by WOO et al [48] followed 29 bronchiectasis patients for up to 16 years and demonstrated remarkable stability of the microbiome over many years of follow-up. The microbiomes of Pseudomonas-and Haemophilus-dominated patients were widely divergent and patients maintained similar profiles over time despite antibiotic treatments [48]. This is consistent with what has been seen with culture, where chronic infection with P. aeruginosa or H. influenzae often persists over many years regardless of therapy [49].…”
Section: Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…While the small sample size of 21 is comparable in size to similar microbiome studies in bronchiectasis, this is unlikely to be sufficiently representative considering that bronchiectasis is a heterogeneous disease and affects millions of people worldwide. Moreover, microbiome characterization by 16S sequencing is not quantitative and the study did not include any measurement of bacterial load, which is strongly linked to lung inflammation and likely treatment response …”
mentioning
confidence: 99%
“…comorbidities, viral/fungal infections and antibiotic treatment) resulting in a low signal-noise ratio; and (iii) lung function itself only weakly correlates with the severity of bronchiectasis and is often not responsive to deterioration or therapy. 10 While the small sample size of 21 is comparable in size to similar microbiome studies in bronchiectasis, 7,11 this is unlikely to be sufficiently representative considering that bronchiectasis is a heterogeneous disease and affects millions of people worldwide. Moreover, microbiome characterization by 16S sequencing is not quantitative and the study did not include any measurement of bacterial load, which is strongly linked to lung inflammation and likely treatment response.…”
mentioning
confidence: 99%